A Pragmatic Analysis of Impoliteness in ’Hamlet’ - Omer, Hanan Khattab (Journal of Tikrit University for Humanities, 2022)
This research is conducted to analyze impoliteness as a pragmatic aspect in the fruitful text ’Hamlet’ since the issue of impoliteness is less researched in comparison with politeness strategies. It is an attempt to providing a framework that can capture impoliteness through an eclectic model. The model is outlined to clarify the concept of impoliteness in such literary text. There are 10 extracts concentrated on Hamlet’s ridicule to Polonius and Ophelia. Each single extract of the data is analyzed by using Leech’s maxims, Culpeper’s strategies, functions and responses as a reaction of impoliteness strategies. This research aims to 1- pinpoint the situations where Leech maxims are violated and utilized to show impoliteness; 2- determine the strategies that are used by the characters in "Hamlet" ; 3- investigate the functions that affect the characters’ use of impoliteness strategies and 4- present the strategies of listeners’ response. This research is an attempt to answer the following questions: How are the maxims employed and violated through the characters’ interactions? What are the strategies of impolite utterances that are submitted by Hamlet? What are the major functions applied by Hamlet’s impolite expressions? What are the most strategies of response used by listeners?. The results of this research reveal that: insult is frequently used as a trigger of impolite acts; tact, approbation and sympathy are frequently violated; bald on record act strategy is mostly acted, and affected function is remarkably noted in Hamlet’s impolite speech. Finally, countering the face attack is frequently utilized by listeners as a defensive strategy of response.